The Development of Administrative Law Training Curriculum for School Administrators - Pornnongsaen, Jedsadaporn; Vajarintarangoon, Kovit; Prachanant, Nawamin (Journal of Buddhist Education and Research (JBER), 2017)
There is a purpose of this research was to study the theories and research related to Administrative Law. The research instruments were used in the research as followed: opinion questionnaire, rating scale questionnaire to estimate Administrative Law training course for school administrators, test, satisfaction questionnaire of school administrators, and verification form to approve the curriculum. The sample was 148 administrators under Surin Primary of Education Service Office Area 3. The statistics to data analyse were percentage, mean, and standard deviation. The research result found that the concept study, theory, researches, Administrative Law training curriculum, related documents, and interviews with 5 experts in administrative law to scope the area of training content by following: Basics of Administrative Law; the National Government Organization Act, BE 2534; Teacher Civil Service and Educational Personnel Act, B.E. 2547; The Administrative Organization of the Ministry of Education Act of B.E. 2546; the Administrative Procedure Act, B.E. 2539; Act on Establishment of Administrative Court and Administrative Court Procedure of Thailand, B.E. 2542; The Liability for Wrongful Act, B.E. 2539; and Official Information Act, B.E. 2540.